A method for preparing basic copper carbonate using copper-containing etching solution

By adopting methods of neutralizing copper deposited reaction, high shear pretreatment and conversion reaction in the treatment of copper-containing etching waste liquid, the process flow is successfully simplified, the cost is reduced, and the purity and singularity of alkaline copper carbonate products is improved, and the problems of complex processes, high costs and numerous heterogeneous phases in the prior art are solved.

CN118791036BActive Publication Date: 2025-03-21CENT SOUTH UNIV
View PDF 3 Cites 0 Cited by

Patent Information

Application Number
CN202410822093.X
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Filing Date
2024-06-24
Publication Date
2025-03-21
Estimated Expiration
2044-06-24

AI Technical Summary

Technical Problem

The existing copper-containing etching waste liquid treatment process is complex, the cost is high, and there are many miscellaneous copper salt products, so the removal of chlorine elements is not thorough.

Method used

By mixing the copper-containing etching liquid with a pH adjuster for neutralization and precipitation of copper, alkali copper chloride slag was obtained, and high shear pretreatment was performed, followed by mixing with sodium carbonate and sodium bicarbonate, and the conversion reaction was carried out under shear conditions to obtain alkali copper carbonate with high purity, few impurities and single phase.

Benefits of technology

The direct synthesis of alkaline copper carbonate from copper-containing etching waste liquid is achieved, which simplifies the process flow, reduces production costs, improves the purity and singularity of the product, and ensures the complete removal of chlorine elements.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN118791036B_ABST
    Figure CN118791036B_ABST
Patent Text Reader

Abstract

The invention belongs to the technical field of preparation of copper-containing compounds, and specifically discloses a method for preparing basic copper carbonate using a copper-containing etching solution. The invention first mixes the copper-containing etching solution with a pH regulator, performs a neutralization and copper precipitation reaction to obtain basic copper chloride slag; then mixes the basic copper chloride slag with water, performs a high shear pretreatment, and obtains a basic copper chloride slurry; then mixes the basic copper chloride slurry with sodium carbonate, sodium bicarbonate and water, and performs a conversion reaction under shear conditions to obtain basic copper carbonate; the copper-containing etching solution of the invention contains chlorine. The invention reduces the generation of impurities such as basic copper carbonate sodium, copper hydroxide and copper oxide during the conversion reaction by controlling the ratio of sodium carbonate and sodium bicarbonate. The high shear treatment avoids the excessive chlorine content in the conversion product, thereby obtaining a basic copper carbonate product with high purity, few impurities and a single phase.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to the technical field of preparation of copper-containing compounds, and in particular to a method for preparing basic copper carbonate by using a copper-containing etching solution. Background Art

[0002] Copper-containing etching waste liquid is the main pollutant generated during the etching process of printed circuit boards (PCBs). According to different etching process requirements, copper-containing etching waste liquid is divided into acidic etching waste liquid and alkaline etching waste liquid. The main components of acidic etching waste liquid are Cu 2+ , H + , CuCl i 2-i (i=1~6), Cl - The main component of alkaline etching waste liquid is Cu 2+ NH4 + 、Cu(NH3) j 2+ (j = 1 to 6), NH3, Cl - Etc. Etching waste liquid has high content of hydrochloric acid or ammonia, is highly corrosive, and contains heavy metal elements such as nickel, lead, zinc, and chromium, and is a typical hazardous waste. On the other hand, etching waste liquid has a high copper content and is also a secondary copper-containing material with resource attributes. Therefore, the comprehensive recycling of copper-containing etching waste liquid has the dual significance of environmental protection and resource circulation.

[0003] At present, there are two technical routes for treating copper-containing etching waste liquid. One is to use electrolysis or extraction-stripping process to extract copper ions from etching waste liquid and regenerate etching liquid at the same time, and the regenerated etching liquid is returned to the PCB etching line for recycling. The other is to directly recover copper powder, basic copper chloride, copper hydroxide, copper oxide, copper sulfate and other copper salt products from etching waste liquid through liquid phase reduction or chemical precipitation, and produce industrial salt byproducts such as sodium chloride, ammonium chloride and ammonium sulfate.

[0004] Chinese patent application CN101391800A discloses a method for producing basic copper chloride and copper sulfate pentahydrate using copper-containing etching waste liquid. Under the condition of strictly controlling the material-liquid ratio and the reaction pH, the invention mixes the acidic etching waste liquid and the alkaline etching waste liquid to precipitate the basic copper chloride product, and then uses sodium hydroxide as a conversion agent to phase-convert the basic copper chloride to obtain copper oxide, and the copper oxide is then acidified with sulfuric acid, crystallized, washed, and dried to obtain the copper sulfate pentahydrate product. The quality of the copper sulfate product extracted by this method can reach the feed-grade copper sulfate standard, but the pretreatment process is complicated, the process flow is long, the reagent consumption is large, and the production cost is high.

[0005] Basic copper carbonate, also known as copper rust and copper green, is not only a precursor for the preparation of various copper-containing compounds, but can also be used as a feed additive, fungicide, wood preservative and dealkalizer. The preparation of basic copper carbonate is mostly based on copper sulfate and copper nitrate as raw materials, and is synthesized through carbonization precipitation reaction. Using copper-containing etching waste liquid as raw material, a direct synthesis method of basic copper carbonate with a simple process flow, a single product phase and low impurity content has been developed, which can realize the high-value utilization of copper-containing etching waste liquid and has important application value. Summary of the invention

[0006] In view of this, the present invention provides a method for preparing basic copper carbonate using a copper-containing etching solution, so as to solve the problems of complex process flow and high cost in the existing method for treating copper-containing etching waste liquid, as well as the problems of more impurities in the copper salt product and incomplete removal of chlorine element.

[0007] In order to achieve the above object, the present invention adopts the following technical solution:

[0008] A method for preparing basic copper carbonate using a copper-containing etching solution comprises the following steps:

[0009] 1) mixing a copper-containing etching solution with a pH regulator to perform a neutralization copper precipitation reaction to obtain basic copper chloride slag;

[0010] 2) mixing the basic cupric chloride slag obtained in step 1) with water and performing high shear pretreatment to obtain basic cupric chloride slurry;

[0011] 3) mixing the basic copper chloride slurry with sodium carbonate, sodium bicarbonate and water, and performing a conversion reaction under shear conditions to obtain basic copper carbonate;

[0012] The copper-containing etching solution contains chlorine element;

[0013] The molar ratio of the sodium carbonate to the sodium bicarbonate is 1-3:1-3.

[0014] Preferably, the temperature of the neutralization copper precipitation reaction in step 1) is 20-90° C., the time of the neutralization copper precipitation reaction is 1-3 hours, and the pH value of the neutralization copper precipitation reaction system is 4-9.

[0015] Preferably, the pH adjuster in step 1) includes one or more of sodium hydroxide, sodium carbonate and hydrochloric acid solution.

[0016] Preferably, the mass volume ratio of the basic cupric chloride slag to water in step 2) is 1 g: 1-5 mL.

[0017] Preferably, the shear rate of the high shear pretreatment in step 2) is 20000-100000s -1 , time is 10 to 30 minutes.

[0018] Preferably, the molar ratio of the total amount of sodium carbonate and sodium bicarbonate to the basic copper chloride in the basic copper chloride slurry in step 3) is 1 to 1.6:1.

[0019] Preferably, the shearing speed in step 3) is 20000-100000s -1 .

[0020] Preferably, the temperature of the conversion reaction in step 3) is 20-90° C., and the time of the conversion reaction is 30-180 min.

[0021] Preferably, the liquid-to-solid ratio in the mixed system in step 3) is 2-10 mL:1 g.

[0022] It can be seen from the above technical solutions that, compared with the prior art, the present invention has the following beneficial effects:

[0023] The invention directly synthesizes a basic copper carbonate product from copper-containing etching waste liquid by a two-step method, and effectively reduces the generation of impurities such as basic copper carbonate sodium, copper hydroxide and copper oxide in the basic copper carbonate product by strictly controlling the ratio of sodium carbonate and sodium bicarbonate (conversion agent) in the basic copper chloride phase conversion process. At the same time, through a high shear reactor, the dispersion of solid phase products is strengthened to prevent basic copper carbonate from being wrapped on the surface of unreacted basic copper chloride to cause excessive chlorine content in the conversion product, thereby obtaining a basic copper carbonate product with high purity, few impurities and single phase. BRIEF DESCRIPTION OF THE DRAWINGS

[0024] In order to more clearly illustrate the embodiments of the present invention or the technical solutions in the prior art, the drawings required for use in the embodiments or the description of the prior art will be briefly introduced below. Obviously, the drawings described below are only embodiments of the present invention. For ordinary technicians in this field, other drawings can be obtained based on the provided drawings without paying creative work.

[0025] Figure 1 The XRD patterns of the basic copper chloride slags in Examples 1 to 6 and Comparative Examples 1 to 4 are as follows;

[0026] Figure 2 The XRD patterns of the basic copper carbonate products in Examples 1 to 6 and Comparative Examples 1 to 4 are shown. DETAILED DESCRIPTION

[0027] The present invention provides a method for preparing basic copper carbonate by using a copper-containing etching solution, comprising the following steps:

[0028] 1) mixing a copper-containing etching solution with a pH regulator to perform a neutralization copper precipitation reaction to obtain basic copper chloride slag;

[0029] 2) mixing the basic cupric chloride slag obtained in step 1) with water and performing high shear pretreatment to obtain basic cupric chloride slurry;

[0030] 3) mixing the basic copper chloride slurry with sodium carbonate, sodium bicarbonate and water, and performing a conversion reaction under shear conditions to obtain basic copper carbonate.

[0031] In the present invention, the copper-containing etching solution contains chlorine element.

[0032] In the present invention, the copper-containing etching solution includes an acidic copper-containing etching solution and / or an alkaline copper-containing etching solution.

[0033] In the present invention, when the copper-containing etching solution is an alkaline copper-containing etching solution, the pH adjuster is preferably a chlorine-containing pH adjuster, and most preferably hydrochloric acid.

[0034] In the present invention, the molar ratio of sodium carbonate to sodium bicarbonate is 1-3:1-3, preferably 1.5-2.5:1.5-2.5, and more preferably 2:2.

[0035] In the present invention, the temperature of the neutralization copper precipitation reaction in step 1) is 20-90°C, specifically 30°C, 40°C, 50°C, 60°C, 70°C, 80°C; the time of the neutralization copper precipitation reaction is 1-3h, specifically 1.2h, 1.5h, 1.8h, 2h, 2.2h, 2.5h, 2.8h; the pH value of the system for the neutralization copper precipitation reaction is 4-9, specifically 5, 6, 7, 8.

[0036] In the present invention, the pH value of the system is the pH value at the reaction end point, and basic copper chloride slag is generated under the condition of a pH value of 4 to 9.

[0037] In the present invention, the pH adjuster in step 1) includes one or more of sodium hydroxide, sodium carbonate and hydrochloric acid solution.

[0038] In the present invention, the mass volume ratio of the basic cupric chloride slag to water in step 2) is 1g:1-5mL, preferably 1g:2-4mL, and more preferably 1g:3mL.

[0039] In the present invention, the shear rate of the high shear pretreatment in step 2) is 20000-100000s -1 , specifically 40000s -1 , 50000s -1 , 60000s -1 , 80000s -1 , 90000s -1; The time is 10 to 30 minutes, specifically 12 minutes, 15 minutes, 18 minutes, 20 minutes, 22 minutes, 25 minutes, and 28 minutes.

[0040] In the present invention, the molar ratio of the total amount of sodium carbonate and sodium bicarbonate in step 3) to the basic cupric chloride in the basic cupric chloride slurry is 1 to 1.6:1, specifically 1.1:1, 1.2:1, 1.3:1, 1.4:1, 1.5:1.

[0041] In the present invention, the shearing speed in step 3) is 20000-100000s -1 , specifically 40000s -1 , 50000s -1 , 60000s -1 , 80000s -1 , 90000s -1 .

[0042] In the present invention, the temperature of the conversion reaction in step 3) is 20-90°C, specifically 30°C, 40°C, 50°C, 60°C, 70°C, 80°C; the time of the conversion reaction is 30-180min, specifically 40min, 50min, 60min, 80min, 100min, 120min, 150min, 160min.

[0043] In the present invention, the liquid-to-solid ratio in the mixed system in step 3) is 2-10 mL:1 g, preferably 4-6 mL:1 g, and more preferably 5 mL:1 g.

[0044] In the present invention, the solid in the liquid-to-solid ratio of the mixed system in step 3) refers to the mass of basic copper chloride.

[0045] The technical solutions in the embodiments of the present invention are described clearly and completely below. Obviously, the described embodiments are only part of the embodiments of the present invention, not all of them. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without creative work are within the scope of protection of the present invention.

[0046] Example 1

[0047] The main element concentrations in alkaline etching waste liquid are Cu 103.17g / L, Cl 156.15g / L, NH4 +135.76g / L, NH3143.05 g / L, the metal impurity contents are Fe 4.77mg / L, Pb 135.22mg / L, Zn 26.08mg / L, Cr0.71mg / L, Na 1878.68mg / L, K 53.81mg / L, Ca 48.42mg / L, Al 35.34mg / L respectively.

[0048] The alkaline etching waste liquid was placed in a reaction container, and hydrochloric acid was slowly added to neutralize the copper precipitation reaction. The reaction temperature was controlled to be 60°C, the end point pH value of the reaction liquid was 5.0, the reaction time was 2h, and the obtained precipitation product was mechanically stirred and washed with 30°C pure water at a liquid-solid ratio of 3:1mL / g for 20min to obtain basic copper chloride slag. The element content and phase composition of the basic copper chloride slag are shown in Table 1 and Appendix. Figure 1 The basic copper chloride slag was prepared with pure water into a slurry with a liquid-to-solid ratio of 3:1 mL / g and added to a high shear reactor at 60,000 s. -1 The shear pretreatment was carried out at a speed of 20 minutes. Then, a mixed solution of sodium carbonate and sodium bicarbonate (the molar ratio of sodium carbonate to sodium bicarbonate was 1:2) was added as a conversion agent, and the molar ratio of basic copper chloride in the basic copper chloride slag to the conversion agent (the total molar ratio of sodium carbonate and sodium bicarbonate) was 1.1:1. Under the conditions of a liquid-solid ratio of the conversion reaction system (the solid in the liquid-solid ratio refers to basic copper chloride, the same below) of 5:1 mL / g and a conversion temperature of 60°C, liquid-solid separation was carried out after 120 minutes of conversion reaction. The obtained conversion product was mechanically stirred and washed with pure water at 30°C for 30 minutes at a liquid-solid ratio of 3:1 mL / g. The washed product was then dried at 30°C for 12 hours. The obtained basic copper carbonate product had element content and phase composition as shown in Table 2 and Attached. Figure 2 As shown, the Cu content is 54.48% and the Cl content is 0.02%, which meets the standard requirements of "Industrial Basic Copper Carbonate" (HG / T4825-2015) Class II products (Cu≥54.0%, Cl≤0.05%), and the physical phase composition is single, without the presence of impurities such as basic sodium copper carbonate, basic copper chloride, copper hydroxide and copper oxide.

[0049] Example 2

[0050] The main element concentrations in the alkaline etching waste liquid are Cu 108.76g / L, Cl 156.23g / L, NH4 + 134.98g / L, NH3138.68 g / L, the metal impurity contents are Fe 4.45mg / L, Pb 132.97mg / L, Zn 25.88mg / L, Cr0.78mg / L, Na 1799.35mg / L, K 54.07mg / L, Ca 47.83mg / L, Al 34.55mg / L respectively.

[0051] The alkaline etching waste liquid was placed in a reaction container, and hydrochloric acid was slowly added to neutralize the copper precipitation reaction. The reaction temperature was controlled to be 60°C, the end point pH value of the reaction liquid was 5.0, the reaction time was 2h, and the obtained precipitation product was mechanically stirred and washed with 30°C pure water at a liquid-solid ratio of 4:1mL / g for 20min to obtain basic copper chloride slag. The element content and phase composition of the basic copper chloride slag are shown in Table 1 and Appendix. Figure 1 The basic copper chloride slag was prepared with pure water into a slurry with a liquid-to-solid ratio of 3:1 mL / g and added to a high shear reactor at 40,000 s. -1 The shear pretreatment was carried out at a speed of 30 minutes. Then, a mixed solution of sodium carbonate and sodium bicarbonate (the molar ratio of sodium carbonate to sodium bicarbonate was 1:3) was added as a conversion agent, and the molar ratio of basic copper chloride in the basic copper chloride slag to the conversion agent (the total molar ratio of sodium carbonate and sodium bicarbonate) was 1:1.3. Under the conditions of a liquid-solid ratio of 4:1 mL / g and a conversion temperature of 60°C in the conversion reaction system, solid-liquid separation was carried out after 120 minutes of conversion reaction. The obtained conversion product was mechanically stirred and washed with pure water at 30°C at a liquid-solid ratio of 2:1 mL / g for 30 minutes. The washed product was then dried at 60°C for 12 hours. The element content and phase composition of the obtained basic copper carbonate product are shown in Table 2 and Attached. Figure 2 As shown, the Cu content is 54.36% and the Cl content is 0.03%, which meets the standard requirements of Class II products (Cu ≥ 54.0%, Cl ≤ 0.05%) of "Industrial Basic Copper Carbonate" (HG / T 4825-2015), and the physical phase composition is single, without the presence of impurities such as basic copper sodium carbonate, basic copper chloride, copper hydroxide and copper oxide.

[0052] Example 3

[0053] The main element concentrations in the acid etching waste liquid are Cu 130.572g / L and Cl 296.211g / L. The metal impurity contents are Fe 27.16mg / L, Pb 112.77mg / L, Zn 46.76mg / L, Cr 2.68mg / L, Na 18.99g / L, K100.35mg / L, Ca 109.97mg / L, and Al 4.09mg / L.

[0054] The acidic etching waste liquid was placed in a reaction container, and sodium hydroxide solution was slowly added to neutralize the copper precipitation reaction. The reaction temperature was controlled to be 60°C, the end point pH value of the reaction liquid was 5.0, the reaction time was 2h, and the obtained precipitation product was mechanically stirred and washed with 30°C pure water at a liquid-solid ratio of 3:1mL / g for 20min to obtain basic copper chloride slag. The element content and phase composition of the basic copper chloride slag are shown in Table 1 and Appendix. Figure 1The basic copper chloride slag was prepared with pure water into a slurry with a liquid-to-solid ratio of 3:1 mL / g, and added to a high shear reactor at 50,000 s. -1 The shear pretreatment was carried out at a speed of 20 minutes. Then, a mixed solution of sodium carbonate and sodium bicarbonate (the molar ratio of sodium carbonate to sodium bicarbonate was 1:2) was added as a conversion agent, and the molar ratio of basic copper chloride in the basic copper chloride slag to the conversion agent (the total molar ratio of sodium carbonate and sodium bicarbonate) was 1:1.1. The conversion reaction was carried out for 120 minutes under the conditions of a liquid-solid ratio of 5:1 mL / g and a conversion temperature of 60°C. The obtained conversion product was mechanically stirred and washed with pure water at 30°C for 30 minutes at a liquid-solid ratio of 3:1 mL / g. The washed product was then dried at 80°C for 12 hours. The element content and phase composition of the obtained basic copper carbonate product are shown in Table 2 and Attached. Figure 2 As shown, the Cu content is 54.24% and the Cl content is 0.02%, which meets the standard requirements of Class II products (Cu ≥ 54.0%, Cl ≤ 0.05%) of "Industrial Basic Copper Carbonate" (HG / T 4825-2015), and the physical phase composition is single, without the presence of impurities such as basic sodium copper carbonate, basic copper chloride, copper hydroxide and copper oxide.

[0055] Example 4

[0056] The main element concentrations in the acid etching waste liquid are Cu 135.382g / L and Cl 302.155g / L. The metal impurity contents are Fe 26.88mg / L, Pb 115.89mg / L, Zn 47.83mg / L, Cr 3.02mg / L, Na 19.03g / L, K103.55mg / L, Ca 115.23mg / L, and Al 4.35mg / L.

[0057] The acidic etching waste liquid was placed in a reaction container, and sodium carbonate solution was slowly added to neutralize the copper precipitation reaction. The reaction temperature was controlled to be 60°C, the end point pH value of the reaction liquid was 5.0, the reaction time was 2h, and the obtained precipitation product was mechanically stirred and washed with 30°C pure water at a liquid-solid ratio of 4:1mL / g for 20min to obtain basic copper chloride slag. The element content and phase composition of the basic copper chloride slag are shown in Table 1 and Appendix. Figure 1 The basic copper chloride slag was prepared with pure water into a slurry with a liquid-to-solid ratio of 3:1 mL / g, and added to a high shear reactor at 50,000 s. -1The shear pretreatment was carried out at a speed of 30 minutes. A mixed solution of sodium carbonate and sodium bicarbonate (the molar ratio of sodium carbonate to sodium bicarbonate was 1:3) was added as a conversion agent, and the molar ratio of basic copper chloride in the basic copper chloride slag to the conversion agent (the total molar ratio of sodium carbonate and sodium bicarbonate) was 1:1.3. The conversion reaction was carried out for 120 minutes under the conditions of a liquid-solid ratio of 5:1 mL / g and a conversion temperature of 50°C. The obtained conversion product was mechanically stirred and washed with pure water at 30°C for 30 minutes at a liquid-solid ratio of 4:1 mL / g. The washed product was then dried at 60°C for 12 hours. The element content and phase composition of the obtained basic copper carbonate product are shown in Table 2 and Appendix. Figure 2 As shown, the Cu content is 54.62% and the Cl content is 0.04%, which meets the standard requirements of Class II products (Cu ≥ 54.0%, Cl ≤ 0.05%) of "Industrial Basic Copper Carbonate" (HG / T 4825-2015), and the physical phase composition is single, without the presence of impurities such as basic sodium copper carbonate, basic copper chloride, copper hydroxide and copper oxide.

[0058] Example 5

[0059] The main element concentrations in the alkaline etching waste liquid are Cu 108.76g / L, Cl 156.23g / L, NH4 + 134.98g / L, NH3138.68 g / L, the metal impurity contents are Fe 4.45mg / L, Pb 132.97mg / L, Zn 25.88mg / L, Cr0.78mg / L, Na 1799.35mg / L, K 54.07mg / L, Ca 47.83mg / L, Al 34.55mg / L respectively.

[0060] The alkaline etching waste liquid was placed in a reaction container, and hydrochloric acid was slowly added to neutralize the copper precipitation reaction. The reaction temperature was controlled to be 20°C, the end point pH value of the reaction liquid was 8.0, the reaction time was 3h, and the obtained precipitation product was mechanically stirred and washed with 30°C pure water at a liquid-solid ratio of 3:1mL / g for 20min to obtain basic copper chloride slag. The element content and phase composition of the basic copper chloride slag are shown in Table 1 and Appendix. Figure 1 The basic copper chloride slag was prepared with pure water into a slurry with a liquid-to-solid ratio of 5:1 mL / g and added to a high shear reactor at 60,000 s. -1The shear pretreatment was carried out at a speed of 20 min. Then, a mixed solution of sodium carbonate and sodium bicarbonate (the molar ratio of sodium carbonate to sodium bicarbonate is 3:2) is added as a conversion agent, the molar ratio of basic copper chloride in the basic copper chloride slag to the conversion agent (the total molar ratio of sodium carbonate and sodium bicarbonate) is 1:1, and under the conditions of a liquid-solid ratio of 10:1 mL / g and a conversion temperature of 90°C in the conversion reaction system, liquid-solid separation is performed after the conversion reaction for 30 minutes, and the obtained conversion product is mechanically stirred and washed with 30°C pure water at a liquid-solid ratio of 3:1 mL / g for 30 minutes, and the washed product is then dried at 30°C for 12 hours to obtain a basic copper carbonate product, wherein the Cu content is 54.39% and the Cl content is 0.02%, which meets the standard requirements of Class II products (Cu≥54.0%, Cl≤0.05%) of "Industrial Basic Copper Carbonate" (HG / T 4825-2015), and the phase composition is single, and no impurities such as basic copper carbonate sodium, basic copper chloride, copper hydroxide and copper oxide appear.

[0061] Example 6

[0062] The main element concentrations in the acid etching waste liquid are Cu 130.572g / L and Cl 296.211g / L. The metal impurity contents are Fe 27.16mg / L, Pb 112.77mg / L, Zn 46.76mg / L, Cr 2.68mg / L, Na 18.99g / L, K100.35mg / L, Ca 109.97mg / L, and Al 4.09mg / L.

[0063] The acidic etching waste liquid was placed in a reaction container, and sodium carbonate solution was slowly added to neutralize the copper precipitation reaction. The reaction temperature was controlled to be 80°C, the end point pH value of the reaction liquid was 7.0, the reaction time was 1h, and the obtained precipitation product was mechanically stirred and washed with 30°C pure water at a liquid-solid ratio of 3:1mL / g for 20min to obtain basic copper chloride slag. The element content and phase composition of the basic copper chloride slag are shown in Table 1 and Appendix. Figure 1 The basic copper chloride slag was prepared with pure water into a slurry with a liquid-to-solid ratio of 1:1 mL / g, and then added to a high shear reactor at 50,000 s. -1The shear pretreatment was carried out at a speed of 30 minutes. Then, a mixed solution of sodium carbonate and sodium bicarbonate (the molar ratio of sodium carbonate to sodium bicarbonate was 1:1) was added as a conversion agent, and the molar ratio of basic copper chloride in the basic copper chloride slag to the conversion agent (the total molar ratio of sodium carbonate and sodium bicarbonate) was 1:1.3. The conversion reaction was carried out for 180 minutes under the conditions of a liquid-solid ratio of 2:1 mL / g and a conversion temperature of 20°C. The obtained conversion product was mechanically stirred and washed with 30°C pure water at a liquid-solid ratio of 3:1 mL / g for 30 minutes, and the washed product was dried at 80°C for 12 hours, wherein the Cu content was 54.21% and the Cl content was 0.02%, which met the standard requirements of Class II products (Cu≥54.0%, Cl≤0.05%) of "Industrial Basic Copper Carbonate" (HG / T 4825-2015), and the phase composition was single, and no impurities such as basic copper carbonate sodium, basic copper chloride, copper hydroxide and copper oxide appeared.

[0064] Comparative Example 1

[0065] The difference between this comparative example and Example 1 is that the sodium bicarbonate added in Example 1 is replaced by an equimolar amount of sodium carbonate.

[0066] The element content and phase composition of basic copper chloride slag during the reaction are shown in Table 1 and Appendix. Figure 1 The element content and phase composition of the obtained basic copper carbonate product are shown in Table 2 and Appendix. Figure 2 As shown, the Cu content is 54.05% and the Cl content is 0.07%, which does not meet the standard requirements of Class II products (Cu≥54.0%, Cl≤0.05%) of "Industrial Basic Copper Carbonate" (HG / T4825-2015). It can be seen that the purity of the basic copper carbonate product generated in Comparative Example 1 is lower than that in Example 1.

[0067] Comparative Example 2

[0068] The difference between this comparative example and Example 2 is that no shearing treatment is performed during the preparation of the basic copper chloride slurry and the conversion reaction, and the reaction is performed under conventional mechanical stirring conditions (200 rpm).

[0069] The element content and phase composition of basic copper chloride slag during the reaction are shown in Table 1 and Appendix. Figure 1 The element content and phase composition of the obtained basic copper carbonate product are shown in Table 2 and Appendix. Figure 2 As shown, the Cu content is 53.02% and the Cl content is 0.04%, which does not meet the standard requirements of Class II products (Cu≥54.0%, Cl≤0.05%) of "Industrial Basic Copper Carbonate" (HG / T4825-2015). It can be seen that the purity of the basic copper carbonate product generated in Comparative Example 2 is lower than that in Example 2.

[0070] Comparative Example 3

[0071] The difference between this comparative example and Example 3 is that the sodium bicarbonate added in Example 3 is replaced by an equimolar amount of sodium carbonate.

[0072] The element content and phase composition of basic copper chloride slag during the reaction are shown in Table 1 and Appendix. Figure 1 The element content and phase composition of the obtained basic copper carbonate product are shown in Table 2 and Appendix. Figure 2 As shown, the Cu content is 54.01% and the Cl content is 0.08%, which does not meet the standard requirements of Class II products (Cu≥54.0%, Cl≤0.05%) of "Industrial Basic Copper Carbonate" (HG / T4825-2015). It can be seen that the purity of the basic copper carbonate product generated in Comparative Example 3 is lower than that in Example 3.

[0073] Comparative Example 4

[0074] The difference between this comparative example and Example 4 is that no shearing treatment is performed during the preparation of the basic copper chloride slurry and the conversion reaction, and the reaction is performed under conventional mechanical stirring conditions (400 rpm).

[0075] The element content and phase composition of basic copper chloride slag during the reaction are shown in Table 1 and Appendix. Figure 1 As shown. The Cu content is 53.65% and the Cl content is 0.04%, which does not meet the standard requirements of Class II products (Cu≥54.0%, Cl≤0.05%) of "Industrial Basic Copper Carbonate" (HG / T 4825-2015). It can be seen that the purity of the basic copper carbonate product generated in Comparative Example 4 is lower than that in Example 4.

[0076] Table 1 Element content of basic copper chloride slag in Examples 1 to 4 and Comparative Examples 1 to 4 (wt%)

[0077] element Cu Cl Fe Pb Zn Cr Na K Ca Al Example 1 48.27 36.06 0.029 0.02 0.03 0.01 4.80 0.01 0.01 0.013 Example 2 49.52 37.32 0.033 0.03 0.01 0.02 4.53 0.01 0.01 0.012 Example 3 48.18 14.33 0.008 0.006 0.02 0.004 3.99 0.02 0.01 0.035 Example 4 48.41 13.58 0.006 0.005 0.02 0.002 4.28 0.01 0.02 0.028 Example 5 48.33 36.24 0.031 0.02 0.02 0.01 4.66 0.01 0.01 0.012 Example 6 48.23 13.96 0.006 0.005 0.02 0.03 4.02 0.02 0.01 0.031 Comparative Example 1 47.16 12.98 0.031 0.02 0.04 0.02 4.92 0.01 0.02 0.014 Comparative Example 2 46.53 8.76 0.052 0.03 0.06 0.06 5.03 0.04 0.05 0.033 Comparative Example 3 37.33 12.66 0.024 0.005 0.05 0.008 5.01 0.02 0.03 0.045 Comparative Example 4 46.12 8.30 0.049 0.008 0.05 0.02 5.36 0.03 0.05 0.051

[0078] Table 2 Element content of basic copper carbonate products in the examples and comparative examples / (wt%)

[0079]

[0080]

[0081] Through Tables 1 to 2 and Figures 1-2 It can be seen that the purity of the basic copper chloride and basic copper carbonate products produced in Examples 1 to 6 is significantly better than that in Comparative Examples 1 to 4.

[0082] The various embodiments in this specification are described in a progressive manner, and each embodiment focuses on the differences from other embodiments. The same or similar parts between the various embodiments can be referenced to each other.

[0083] The above description of the disclosed embodiments enables one skilled in the art to implement or use the present invention. Various modifications to these embodiments will be apparent to one skilled in the art, and the general principles defined herein may be implemented in other embodiments without departing from the spirit or scope of the present invention. Therefore, the present invention will not be limited to the embodiments shown herein, but rather to the widest scope consistent with the principles and novel features disclosed herein.

Claims

1. A method for preparing basic copper carbonate using a copper-containing etching solution, characterized in that: The steps include: 1) mixing a copper-containing etching solution with a pH regulator to perform a neutralization copper precipitation reaction to obtain basic copper chloride slag; 2) mixing the basic cupric chloride slag obtained in step 1) with water and performing high shear pretreatment to obtain basic cupric chloride slurry; 3) mixing the basic copper chloride slurry with sodium carbonate, sodium bicarbonate and water, and performing a conversion reaction under shear conditions to obtain basic copper carbonate; The copper-containing etching solution contains chlorine element; The molar ratio of sodium carbonate to sodium bicarbonate is 1-3:1-3; The shear rate of the high shear pretreatment in step 2) is 20000-100000s -1 , time is 10 to 30 minutes; The molar ratio of the total amount of sodium carbonate and sodium bicarbonate to the basic copper chloride in the basic copper chloride slurry in step 3) is 1 to 1.6:1; The shearing speed in step 3) is 20000~100000s -1 .

2. The method for preparing basic copper carbonate using a copper-containing etching solution according to claim 1, characterized in that: The temperature of the neutralization copper precipitation reaction in step 1) is 20-90° C., the time of the neutralization copper precipitation reaction is 1-3 hours, and the pH value of the neutralization copper precipitation reaction system is 4-9.

3. The method for preparing basic copper carbonate using a copper-containing etching solution according to claim 2, characterized in that: The pH adjuster in step 1) includes one or more of sodium hydroxide, sodium carbonate and hydrochloric acid solution.

4. The method for preparing basic copper carbonate using a copper-containing etching solution according to claim 3, characterized in that: The mass volume ratio of the basic cupric chloride slag to water in step 2) is 1 g: 1-5 mL.

5. The method for preparing basic copper carbonate using a copper-containing etching solution according to claim 1, characterized in that: The temperature of the conversion reaction in step 3) is 20-90° C., and the time of the conversion reaction is 30-180 min.

6. A method for preparing basic copper carbonate using a copper-containing etching solution according to claim 1 or 5, characterized in that: The liquid-to-solid ratio in the mixed system in step 3) is 2-10 mL:1 g.

Citation Information

Patent Citations

  • Method for producing basic copper chloride, cupric sulfate pentahydrate from copper-containing etching waste liquid

    CN101391800A

  • Method for converting basic copper chloride into basic copper carbonate

    CN106673048A

  • Shearing separation belt cleaning device of material is retrieved in regeneration

    CN205762664U